Immunogenetics of gastrointestinal cancers: A systematic review and retrospective survey of inborn errors of immunity in humans. Issue 6 (13th April 2022) - Zheng, Beishi; Artin, Michael G; Chung, Howard; Chen, Bing; Sun, Siming; May, Benjamin L; Hur, Chin; Green, Peter H R; Wang, Timothy C; Park, Jiheum; Kong, Xiao‐Fei
Abstract: Background and Aim: Humans with inborn errors of immunity (IEI), or primary immunodeficiencies, may be associated with a potential risk factor for early‐onset gastrointestinal (GI) cancer. Methods: We systematically reviewed all cases with clinical diagnoses of both an IEI and a GI cancer in three databases (MEDLINE, SCOPUS, and EMBASE). In total, 76 publications satisfying our inclusion criteria were identified, and data for 149 cases were analyzed. We also searched our institutional cancer registry for such cases. Results: We identified 149 patients with both an IEI and a GI cancer, 95 presented gastric cancer, 13 small bowel cancer, 35 colorectal cancer, and 6 had an unspecified cancer or cancer at another site. Gastric and colon adenocarcinomas were the most common. For both gastric and colorectal cancers, age at onset was significantly earlier in patients with IEIs than in the general population, based on the SEER database. Common variable immunodeficiency (CVID) was the most common IEI associated with gastrointestinal cancer. About 12% of patients had molecular genetic diagnoses, the three most frequently implicated genes being ATM, CARMIL2, and CTLA4 . Impaired humoral immunity and Epstein–Barr virus (EBV) infection were frequently reported as factors potentially underlying early‐onset GI cancers in patients with IEIs. We identified one patient with CVID and early‐onset gastric adenocarcinoma, recurrent diarrhea, and gastrointestinal CMV infection from a retrospective survey. Conclusion: Patients with IEIs should be considered at risk of early‐onset GI cancers and should therefore undergo cancer screening at an earlier age.